Analytical approaches for flexural analysis of RC slabs strengthened with prestressed or non-prestressed CFRP laminates - Dushimimana, Aloys (2022)
The 15th International Conference on Fibre-Reinforced Polymers for Reinforced Concrete Structures (FRPRCS-15) & The 8th Asia-Pacific Conference on FRP in Structures (APFIS-2022), 10-14 December 2022, Shenzhen, China.